Proceedings of the XXV International Symposium on Lattice Field Theory — PoS(LATTICE 2007) 2008
DOI: 10.22323/1.042.0002
|View full text |Cite
|
Sign up to set email alerts
|

Hadron interactions from lattice QCD

Abstract: Progress on the potential method, recently proposed to investigate hadron interactions in lattice QCD, is reviewed. The strategy to extract the potential in lattice QCD is explained in detail. The method is applied to extract N N potentials, hyperon potentials and the meson-baryon potentials. A theoretical investigation is made to understand the origin of the repulsive core using the operator product expansion. Some recent extensions of the method are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A nonperturbative test of the RI/SMOM scheme for the quark mass renormalization can be found in Ref. [17].…”
Section: Introductionmentioning
confidence: 99%
“…A nonperturbative test of the RI/SMOM scheme for the quark mass renormalization can be found in Ref. [17].…”
Section: Introductionmentioning
confidence: 99%
“…In [13,14], it is shown that the energy-dependent potential can be converted to the energy-independent but non-local potential as…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the BS wave function defined above can be interpreted as the N N scattering wave. Based on the above fact, we have proposed the following strategy to define and extract the N N potential in QCD [14,15] . We define a non-local potential from the BS wave function as…”
Section: Strategy To Extract Potentials In Qcdmentioning
confidence: 99%